Parameters of Spectral Analysis of Heart Rate Variability in Rats - Чиж, М.О. (Problems of Cryobiology and Cryomedicine, 25(3): 235–245. https://doi.org/10.15407/cryo25.03.235, 2015)
The paper considers the synthesis and analysis of the reported data on the use of the parameters of spectral analysiswhen studying the heart rate variability (HRV) in rats. There were demonstrated the criteria for electrocardiographic equipment toperform studies in small mammals, substantiated the indices of duration of electrocardiogram (ECG) recording and indicated thenecessity in stationary state of animals during ECG recording. When describing the ranges of spectral frequencies and data-basedreports we suggested the parameters of HRV spectral analysis during 5-minute ECG recording in conscious rats such as: TP – 0.015–3 Hz; VLF – 0.015–0.04 Hz; LF – 0.05–0.79 Hz; HF – 0.8–3 Hz. The paper pointed to the need of performing extra-studies on the Mayerwave frequency, as well as the expediency of HRV spectral analysis together with respiration diagram recording. To clarify theparameters of spectral frequencies we recommended the findings comparing with the results of other research methods of HRV. Thedata of statistical processing of cardiointervalograms during ECG recording in unrestrained rats will enable to specify the selectedparameters, accept a common protocol of HRV spectral analysis in this animal species and evaluate their vegetative status. /////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////// Статья посвящена обобщению и анализу литературных данных по использованию параметров спектрального анализа при исследовании вариабельности сердечного ритма (ВСР) у крыс. Приведены критерии электрокардиографической аппаратуры для проведения экспериментов над мелкими млекопитающими, обоснованы показатели длительности записи электрокардиограммы (ЭКГ) и указана необходимость стационарного состояния животных во время регистрации ЭКГ. Описаны диапазоны спектральных частот и на основании данных литературных источников предложены параметры спектрального анализа ВСР при 5-минутной записи ЭКГ у крыс в состоянии бодрствования: ТР – 0,015–3 Гц; VLF – 0,015–0,04 Гц; LF – 0,05–0,79 Гц; HF – 0,8–3 Гц. В статье указано на необходимость дополнительных исследований по изучению диапазонов волн Майера, а также целесообразность проведения спектрального анализа ВСР одновременно с записью графика дыхания. Для уточнения параметров спектральных частот рекомендовано сопоставлять полученные данные с результатами других методов исследования ВСР. Данные статистической обработки кардиоинтервалограмм при регистрации ЭКГ у крыс в свободном поведении позволит уточнить выбранные параметры и утвердить единый протокол спектрального анализа ВСР у данного вида животных и оценить их вегетативный статус. /////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////// Стаття присвячена узагальненню та аналізу літературних даних щодо використання параметрів спектрального аналізу при дослідженні варіабельності серцевого ритму (ВСР) у щурів. Наведено критерії електрокардіографічної апаратури для проведення експериментів на дрібних ссавцях, обґрунтовано показники тривалості запису електрокардіограми (ЕКГ) та необхідність стаціонарного стану тварин під час дослідження. Описані діапазони спектральних частот і на підставі даних літературних джерел запропоновано параметри спектрального аналізу ВСР при 5-хвилинному записі ЕКГ у щурів, які знаходяться у стані неспання: ТР – 0,015–3 Гц; VLF – 0,015–0,04 Гц; LF – 0,05–0,79 Гц; HF – 0,8–3 Гц. У статті вказано на необхідність додаткових досліджень з вивчення діапазонів хвиль Майєра, а також на доцільність проведення спектрального аналізу ВСР одночасно з записом графіка дихання. Для уточнення параметрів спектральних частот рекомендовано порівнювати отримані дані з результатами інших методів дослідження ВСР. Дані статистичної обробки кардіоінтервалограмм, які були отримані під час реєстрації ЕКГ у щурів у вільній поведінці, дозволять уточнити вибрані параметри та затвердити єдиний протокол спектрального аналізу ВСР у даного виду тварин і оцінити їх вегетативний статус.
Параметры спектрального анализа вариабельности сердечного ритма у крыс
Chizh, N. A. (2015). Parameters of Spectral Analysis of Heart Rate Variability in Rats. Problems of Cryobiology and Cryomedicine, 25(3), 235–245. https://doi.org/10.15407/cryo25.03.235
Keywords: heart rate variability; spectral analysis; frequency ranges; rats; вариабельность сердечного ритма; спектральный анализ; частотные диапазоны; крысы